Proteomic Insights into the Effects of Jianweixiaoshi Tablets on Functional Dyspepsia with Spleen Deficiency in Rats - Cheng X; Wan J; Sun D; Zhan Y; Yu J; Li Y; Xiong Y; Liu W (Drug Design, Development and Therapy)
Xiaoying Cheng,1,2,* Jianhua Wan,1,2,* Denglong Sun,1,2 Yang Zhan,1,2 Jingting Yu,1,2 Yingmeng Li,1,2 Yanxia Xiong,1,2 Wenjun Liu1,2 1State Key Laboratory for the Modernization of Classical and Famous Prescriptions of Chinese Medicine, Nanchang, 330096, People’s Republic of China; 2Research and Development Department, Jiangzhong Pharmaceutical Co., Ltd., Nanchang, 330103, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wenjun Liu, Email crjzliuwenjun@163.comBackground: Jianweixiaoshi tablets (JWXS) is widely used in traditional Chinese medicine for treating functional dyspepsia with spleen deficiency (SD-FD) in China. However, the molecular mechanisms underlying the therapeutic effects of JWXS remain incompletely understood.Methods: Functional dyspepsia was induced in rats with spleen deficiency by iodoacetamide in combination with the modified multiple platform method. The SD-FD rats were administered JWXS at both low and high doses, as well as domperidone. We conducted a comprehensive evaluation of the treatment effects of JWXS, including body weight, gastrointestinal motility, immune organ index, biochemical analysis, gastrointestinal hormones, and hematological studies. Quantitative proteomic analysis based on data-independent acquisition (DIA) was used to determine the changes in protein profiles of gastric and duodenal tissues in SD-FD rats and JWXS intervention rats.Results: The results showed that JWXS effectively alleviated gastrointestinal motility disorders in SD-FD rats, as indicated by accelerated gastric emptying and intestinal propulsion, increased levels of gastrin, motilin, and ghrelin, and reduced levels of cholecystokinin-octapeptide, vasoactive intestinal peptide, and somatostatin. Additionally, JWXS increased the spleen and thymus index, increased %lymphocyte in blood, reduced white blood cell count and %neutrophil, and improved immune function. Through quantitative proteomic analysis of gastric tissues, we identified 333 differentially expressed proteins in the JWXS treatment group and the model group. Notably, the mechanism by which JWXS accelerated gastric emptying may be related to PLC-γ and SERCA2 in the calcium signaling pathway. Furthermore, JWXS treatment altered the expression of 732 proteins in rat duodenal samples. The differentially expressed proteins were enriched in immune-related functions and pathways, including antigen processing and presentation, as well as the intestinal immune network for IgA production.Conclusion: In conclusion, JWXS exhibits a multi-faceted impact on various pathways, demonstrating its efficacy in treating SD-FD. These findings provide a foundation for the clinical application of JWXS in managing SD-FD.Keywords: Jianweixiaoshi tablets, functional dyspepsia, spleen deficiency, traditional Chinese medicine, proteomic